2017
DOI: 10.5194/wes-2-533-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the low-level jet's negative wind shear on the wind turbine

Abstract: Abstract.Nocturnal low-level jets (LLJs) are defined as relative maxima in the vertical profile of the horizontal wind speed at the top of the stable boundary layer. Such peaks constitute major power resources for wind turbines. However, a wind speed maximum implies a transition from positive wind shears below the peak to negative ones above. The effect that such a transition has on wind turbines has not been thoroughly studied.This research study employed a methodical approach to the study of negative wind sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
(26 reference statements)
3
29
0
Order By: Relevance
“…Wind shear and turbulence intensity associated with low-level jets also differ substantially from that assumed under 'standard' conditions. Low-level jets modify wind power performance and loading by impacting wake recovery rates and vertical profiles of wind 5 speed, direction and turbulence (Wharton and Lundquist, 2012;Bhaganagar and Debnath, 2014;Park et al, 2014;Gutierrez et al, 2017). Thus, for a complete assessment of loads and power, it is important to have a broad understanding of the sitespecific low-level jet characteristics: how often do they occur, under which circumstances, at what height and with what strength, and what mechanisms are responsible for their formation?…”
Section: Introductionmentioning
confidence: 99%
“…Wind shear and turbulence intensity associated with low-level jets also differ substantially from that assumed under 'standard' conditions. Low-level jets modify wind power performance and loading by impacting wake recovery rates and vertical profiles of wind 5 speed, direction and turbulence (Wharton and Lundquist, 2012;Bhaganagar and Debnath, 2014;Park et al, 2014;Gutierrez et al, 2017). Thus, for a complete assessment of loads and power, it is important to have a broad understanding of the sitespecific low-level jet characteristics: how often do they occur, under which circumstances, at what height and with what strength, and what mechanisms are responsible for their formation?…”
Section: Introductionmentioning
confidence: 99%
“…Local maxima at wind turbine hub heights were shown by Wagner et al (2009) to significantly impact the power output due to the impact the negative shear has on the available energy across the rotor area. The inflections can however also have positive consequences as Gutierrez et al (2017) found the negative shear in the top half of a low-level jet to dampen motion, forces and moments acting on the turbine tower and nacelle.…”
Section: Height Of Local Maximum 15mentioning
confidence: 99%
“…The increased occurrence of local maxima at higher elevations should be a concern as these elevations are within common rotor swept areas of modern turbines and can have a direct impact on the available energy in the wind. The impact on the turbine loads may however not be only negative, 15 as Gutierrez et al (2017) showed that a negative shear dampened motion, moments and forces acting on the turbine tower and nacelle.…”
Section: Offshore Sitesmentioning
confidence: 99%
“…Local maxima at wind turbine hub heights were by Wagner et al (2009) shown to significantly impact the power output due to the impact the negative shear has on the available energy across the rotor area. The inflections can however also have positive consequences as Gutierrez et al (2017) found the negative shear in the top half of a low-level jet to dampen motion, forces and moments on the turbine tower and nacelle. Figure 6a shows the height occurrence of local maximum at the onshore sites.…”
Section: Height Of Local Maximummentioning
confidence: 99%